Helminth communities in the burrowing toad, Rhinella fernandezae, from Northeastern Argentina - Hamann, Monika Ines (2013)
The main goals of this study were to determine the richness and diversity of helminth parasites of Rhinella fernandezae at the component and infracommunity levels and determine the ecological implications of different biotic and abiotic factors. Specimens were collected near the city of Corrientes, Corrientes Province, Argentina. Prevalence of infection was 94% in the specimens examined (n = 65). The helminth component community in R. fernandezae in this area was comprised a total of 22 species. Of all helminth species, only three (Catadiscus inopinatus, Cosmocerca podicipinus and C. parva) were dominant (importance value: I > 1.0) in the community. The most abundant species were B. tetracotyloides (d = 0.43) among the larvae and C. podicipinus (d = 0.09) among adult worms. At the infracommunity level, the mean individual species richness (2.28 ± 1.48) (mean±SD) was no more than 3 helminth species per infected host; the diversity and equitability of helminths were 0.23 ± 0.21 and 0.48 ± 0.38, respectively. The host body size was the main factor in determining the parasite abundance. Species richness was significantly and positively correlated with host body size. The parasite helminth species predominantly showed an overdispersed pattern of distribution. Helminth species showed two negative and significant pairs of covariation and one significant pair of association (P 0.05). R. fernandezae has a wide variety of parasites relating to the host microhabitat, mobility and feeding habits.